Design and simulation of mechanical components of a robotic cell for the automotive industry. - Reyna Martínez, José Israel (2018)
Process automation is very common in industries that seek to increase quality and reduce costs, these companies often bet on generating their own technology to ensure that they consider all the requirements that need to be met and also, they allow can adapt the technology to the requirements that arise. The design of work cell will allow maintaining the production of current models of glass, but in turn, will be adjusted for the manufacture of new models of automotive glass. To be sure that the process automation is effective, an appropriate design is required, as well as an analysis to optimize the models and verify that the design meets the requirements. This work will try to comply with the design of an automated work cell flexible in production, current, and future, but also optimized in size and cost, all using a set of design and simulation tools for process validation that will be generated at the end of the work.